A Comparison of Computational and Experimental Fluid Dynamics Studies between Scaled and Original Wing Sections, in Single-Phase and Two-Phase Flows, and Evaluation of the Suggested Method - Dionysios G. Karkoulias; Anastasios G. Panagiotopoulos; Andreas I. Giannaros; Dionissios P. Margaris (Computation, 2022)
The correlation between computational fluid dynamics (CFD) and experimental fluid dynamics (EFD) is crucial for the behavior prediction of aerodynamic bodies. This paper’s objective is twofold: (1) to develop a method that approaches commercial CFD codes and their link with EFD in a more efficient way, using a downscaled model, and (2) to investigate the effect of rain on the aerodynamic behavior of a wing. More specifically, we investigate the one-phase and two-phase flow over a typical wing section NACA 641-212 airfoil, in the commercial code Ansys Fluent. Two computational models were developed; the first model represents the original dimensions of the wing, while the second is downscaled to 23% of the original. The response of the models in air and air–water flow were primarily studied, as well as the impact on aerodynamic efficiency due to the existence of the second phase. For the computational fluid dynamics simulations, a pressure-based solver with a second-order upwind scheme for the spatial discretization and the Spalart–Allmaras (SA) turbulence model were utilized. Meanwhile, for the two-phase flow of air–water, the discrete phase model (DPM) with wall–film boundary conditions on the surface of the wing and two-way coupling between continuous and discrete phase was considered. The second phase was simulated as water droplets injected in the continuous phase, in a Euler–Lagrange approach. The experimental model was constructed in accordance with the downscaled model and tested in a subsonic wind tunnel, using 3D printing technology which reduced the experiment expenses. The presence of water in two-phase flow was proven to deteriorate the aerodynamic factors of the wing compared to one-phase flow, as expected. The three-stage comparison of CFD and EFD results showed a very good convergence, in both single and two-phase flow. This can lead to the conclusion that a rapid and low-cost study for the estimation of the aerodynamic performance of objects with high accuracy is feasible with the suggested method.